KEWENANGAN PENYIDIK BADAN NARKOTIKA NASIONAL DALAM MEMBERIKAN REHABILITASI TERHADAP PECANDU NARKOTIKA BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Riza, Iwan Lesmana; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Drug addicts are "self-victimizing Victims ",because drug addicts suffering from dependence syndrome as a result of drug abuse does himself. Article 54 of Law No. 35 of 2009 on Narcotics ( Narcotics Act ) states that : " narcotics addicts and drug abusers shall undergo medical rehabilitation and social rehabilitation". There are two issues raised in this study. First, how does a drug abuser can be said to be a drug addict ?. Second, how is the authority Investigators National Narcotics Agency ( BNN ) in the rehabilitation of narcotic addicts based on Law No. 35 of 2009 on Narcotics ?. Third, how is the procedure for the determination of drug addicts and rehabilitation requirements for someone to be rehabilitated by BNN ?. The research method used in this study is a qualitative study using normative juridical law derived from the data of secondary and primary legal data.From the results of the research can be submitted that a person can be said to be a drug abuser drug addicts are referring to the Decree of the Minister of Health of the Republic of Indonesia Number 422/menkes/sk/iii/2010 on Guidelines for Medical Management of Drug Use Disorders. Decisions concerning the implementation of the rehabilitation of the Narcotic Addict is guided by Article 13 paragraph ( 4 ) of Government Regulation Nonor 25 in 2011. Later in the Narcotics Law Article 75 states that BNN has the authority to conduct investigations and inquiries abuse of narcotic drugs and precursors previously independent investigative authority is the authority of the police. Further, the terms and procedures for the rehabilitation of drug addicts do is set the Narcotics Act and the Supreme Court Circular ( SEMA ) No. 07 of 2009 and the latest is the release of SEMA No. 04 Year 2010, which is a revision of the SEMA No. 07 of 2009.Keywords : Authority - Providing - Rehabilitation - Addicts - Narcotics